Feasibility to Use Continuous Magnetotelluric Observations for Monitoring Hydrothermal Activity. Numerical Modeling Applied to Campi Flegrei Volcanic System (Southern Italy) - Carbonari, Rolando; Di Maio, Rosa; Piegari, Ester (Frontiers in Earth Science, 2019)
The magnetotelluric (MT) method is useful for monitoring geophysical processes because of a large dynamic depth range. In this paper, a feasibility study of employing continuous MT observations to monitor hydrothermal systems for both volcanic hazard assessment and geothermal energy exploitation is presented. Sensitivity of the MT method has been studied by simulating spatial and temporal evolution of temperature and gas saturation distributions in a hydrothermal system, and by calculating the MT response at different time steps. Two possible scenarios have been considered: the first is related to an increase in the fluid flow rate at the system source, the second is associated to an increase in the permeability of the rocks hosting the hydrothermal system. Numerical simulations have been performed for each scenario, and the sensitivity of the MT monitoring has been analyzed by evaluating the time interval needed to observe significant variations in the MT response. This study has been applied to the hydrothermal system of the Campi Flegrei (southern Italy) and it has shown that continuous MT measurements are not sensitive enough to detect a significant increase in the source fluid flow rate over time intervals less than ten years. On the contrary, if the permeability of the upwelling zone increases, a measurable change in the MT response occurs over a time interval ranging from six months to three years, depending on the extent of the permeability increase. Such findings are promising and suggest that continuous MT observations in active volcanic areas can be useful for imaging volcano-hydrothermal system activity.